"Phenotyping" Hospital Value of Care for Patients with Heart Failure. (28th June 2014) - Xu, Xiao; Li, Shu‐Xia; Lin, Haiqun; Normand, Sharon‐Lise T.; Kim, Nancy; Ott, Lesli S.; Lagu, Tara; Duan, Michael; Kroch, Eugene A.; Krumholz, Harlan M.
<x xml:space="preserve">Abstract</x> Objective To characterize hospitals based on patterns of their combined financial and clinical outcomes for heart failure hospitalizations longitudinally. Data Source Detailed cost and administrative data on hospitalizations for heart failure from 424 hospitals in the 2005–2011 Premier database. Study Design Using a mixture modeling approach, we identified groups of hospitals with distinct joint trajectories of risk‐standardized cost (RSC) per hospitalization and risk‐standardized in‐hospital mortality rate (RSMR), and assessed hospital characteristics associated with the distinct patterns using multinomial logistic regression. Principal Findings During 2005–2011, mean hospital RSC decreased from 12, 003 to 10, 782, while mean hospital RSMR declined from 3.9 to 3.2 percent. We identified five distinct hospital patterns: highest cost and low mortality (3.2 percent of the hospitals), high cost and low mortality (20.4 percent), medium cost and low mortality (34.6 percent), medium cost and high mortality (6.2 percent), and low cost and low mortality (35.6 percent). Longer hospital stay and greater use of intensive care unit and surgical procedures were associated with phenotypes with higher costs or greater mortality. Conclusions Hospitals vary substantially in the joint longitudinal patterns of cost and mortality, suggesting marked difference in value of care. Understanding determinants of the variation will inform strategies for improving the value of hospital care.